Decentralized enterprise risk management issues under rapidly changing environments - Levente Bakos; Dănuț Dumitru Dumitrașcu (Risks, 2021)
Under the growing complexity of manufacturing processes, supply chains, markets and stakeholder expectations, enterprise risk management (ERM) has become an extremely important, probably yet still underdeveloped, management function. Enterprise risk management theory and practice should keep pace with the changes of rapidly changing environments, through new, more adaptive approaches. The article presents some of the results of a longitudinal survey at Eastern-European manufacturing organizations made on risk management techniques. The goal of the research was the study of risk management techniques under rapidly changing environments in highly standardized industries (pharmaceutical and automotive). The research was focused on the role of human resources in handling technology-related/operational risks and to what extent a decentralized risk management is present. Multidisciplinary cooperation, the selection of the teams, communication and the decision making within the team was analysed. During our research few common risk analysis routines were identified at the studied organizations. Through an interview-based qualitative survey, possible weaknesses of common risk identification techniques were identified. The article presents three risk evaluation methods with the same features. The answers provided during the interviews indicate that risk assessment techniques are mostly centralized (coordinated by a single person/unit), linear (based on If-Then construct) and rigid, definitively not suitable when quick changes are in the organization environment.
Keywords: 330; decentralized risk assessment; enterprise risk management; linear thinking